Dora Marsden and The Freewoman: Editing Policy and Ideological Pluralism (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Dora Marsden and Mary Gawthorpe, two famous suffragettes, left the Women’s Social and Political Union in 1911. In the same year they established their journal The Freewoman – A Weekly Feminist Review. Central to this journal was the possibility of a dialogue and debate. In less than a year, this journal stirred up an intense debate on the numerous feminist-related questions and problems: who is the Freewoman, what are the accepted models of morality and sexuality and how one can challenge those, why women’s financial independence matters etc. The journal lasted only one year. This essay discusses the complex relationship between Dora Marsden’s personal life and her intellectual work, and aims to describe and analyse Marsden’s politics of editing.
Keywords: The Freewoman (1911-1912); Dora Marsden; editing policy; discussion as strategy; free woman identity